Diatomite‐Templated Synthesis of Freestanding 3D Graphdiyne for Energy Storage and Catalysis Application. Issue 20 (30th March 2018) - Li, Jiaqiang; Xu, Jing; Xie, Ziqian; Gao, Xin; Zhou, Jingyuan; Xiong, Yan; Chen, Changguo; Zhang, Jin; Liu, Zhongfan
Abstract: Graphdiyne (GDY), a new kind of two‐dimensional (2D) carbon allotropes, has extraordinary electrical, mechanical, and optical properties, leading to advanced applications in the fields of energy storage, photocatalysis, electrochemical catalysis, and sensors. However, almost all reported methods require metallic copper as a substrate, which severely limits their large‐scale application because of the high cost and low specific surface area (SSA) of copper substrate. Here, freestanding three‐dimensional GDY (3DGDY) is successfully prepared using naturally abundant and inexpensive diatomite as template. In addition to the intrinsic properties of GDY, the fabricated 3DGDY exhibits a porous structure and high SSA that enable it to be directly used as a lithium‐ion battery anode material and a 3D scaffold to create Rh@3DGDY composites, which would hold great potential applications in energy storage and catalysts, respectively. Abstract : Freestanding three‐dimensional graphidyne (3DGDY) is successfully prepared using naturally abundant and inexpensive diatomite as a template. The fabricated 3DGDY exhibits a porous structure and high specific surface area that enable the 3DGDY to be applied as a potential lithium‐ion battery anode material and an ideal 3D scaffold to create Rh@3DGDY composites with high catalytic and recyclable performance.